Efeitos do contato pele a pele imediato entre mãe e recém-nascido: uma revisão sistemática - Bezerra, Cinthia Daniele da Silva (2025)
Introduction: Skin-to-skin contact in the first hour of life is essential for the baby's adaptation to the transition from intrauterine to extrauterine life. However, it is observed that there is controversy about adherence, correct execution and benefits of this contact for mothers and newborns. Given these conflicts, this systematic review aims to evaluate the effects of immediate skin-to-skin contact between mother and newborn in the first hour of life and is based on the following review question: What are the effects of immediate skin-to-skin contact between mother and newborns in the first hour of life? Method: This is a systematic review, whose inclusion criteria were randomized or quasirandomized clinical trials on the topic. The search, collection and analysis of data were carried out by two reviewers and a third reviewer mediated the disagreements. The search was carried out in the following information sources: PubMed/Medline, Web of Science, Cumulative Index to Nursing and Allied Health Literature (CI-NAHL), Latin American and Caribbean Literature in Health Sciences (LILACS), Scopus, Scientific Electronic Library (SciELO), Embase and The Cochrane Library. For the purposes of this study, the searches carried out in PubMed/Medline, Embase and the Virtual Health Library will be presented. A data extraction form was developed to extract the data from the selected studies, which were synthesized in a table and presented descriptively. Results: A total of 2,359 studies were identified. After removing duplicates, the selection process was based on the title and abstract of 1,995 studies. Then, a full-text screening was performed on 26 studies. Seventeen of them were not included because they were not available in full. Finally, nine studies met the eligibility criteria. More than 65% (n=6) of the studies evaluated skin-to-skin contact in infants born vaginally. Breastfeeding was the outcome in 100% of the articles and neonatal thermoregulation in two studies. The articles evaluated early initiation of breastfeeding and exclusive breastfeeding among other variables influenced by skin-to-skin contact. Final Considerations: The effects of skin-to-skin contact on breastfeeding were identified: early initiation of breastfeeding, longer duration of the first feeding, better breastfeeding and sucking capacity, higher rates of exclusive breastfeeding, better self-efficacy and greater success in breastfeeding. Regarding neonatal thermoregulation, there were no risks of hypothermia for the newborn in the CPP. Protocol registration: PROSPERO - CRD42024561462.